1999
DOI: 10.1002/jlb.66.1.127
|View full text |Cite
|
Sign up to set email alerts
|

No detectable NO synthesis from L-arginine or NG-hydroxy-L-arginine in fMLP-stimulated human blood neutrophils despite production of nitrite, nitrate, and citrulline from NG-hydroxy-L-arginine

Abstract: Nitric oxide (NO) is a well-documented effector molecule in rodent phagocytes but its synthesis in human neutrophils has been controversial. In this study, NO production in human neutrophils activated by chemotactic peptide N-formyl-methionyl-leucyl-phenylalanine (fMLP) was measured in the presence of L-arginine (L-Arg) and N(G)-hydroxy-L-arginine (OH-L-Arg), the precursor and intermediate amino acids in NO synthesis, respectively. Incubation of fMLP-activated neutrophils with OH-L-Arg resulted in a production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 40 publications
2
15
1
Order By: Relevance
“…4a). These observations are consistent with previous investigators who have reported that NO production by human blood neutrophils is not influenced by fMLP or by inhibitors of NOS activity (Holm et al 1999;Padgett and Pruett 1995). In contrast, Schmidt et al (1989) reported increased neutrophil-derived NO after fMLP stimulation.…”
Section: Contribution Of Rnssupporting
confidence: 94%
See 1 more Smart Citation
“…4a). These observations are consistent with previous investigators who have reported that NO production by human blood neutrophils is not influenced by fMLP or by inhibitors of NOS activity (Holm et al 1999;Padgett and Pruett 1995). In contrast, Schmidt et al (1989) reported increased neutrophil-derived NO after fMLP stimulation.…”
Section: Contribution Of Rnssupporting
confidence: 94%
“…Human neutrophils are capable of producing relatively high concentrations of ROS (Rosen et al 1995) and have been demonstrated to cause injury to a variety of cell types (Entman et al 1992;Murphy et al 1999), including cultured skeletal muscle (Pizza et al 2001). Although controversial, human neutrophils appear to lack nitric oxide synthase (NOS) activity (Yan et al 1994) and the ability to produce nitric oxide (NO) (Holm et al 1999;Miles et al 1995;Sethi and Dikshit 2000;Yan et al 1994). On the other hand, human skeletal muscle is known to express high levels of neuronal NOS (nNOS) (Frandsen et al 1996;Nakane et al 1993) and to increase production of NO after contraction-induced muscle injury (Radak et al 1999).…”
Section: Introductionmentioning
confidence: 97%
“…Similar phenomenon have been observed in platelets, in which cAMP-dependent protein kinase (PKA) is largely responsible for the inhibition of platelet activation while PKG plays a stimulatory role under several conditions, both in vitro and in vivo (61,62). In neutrophils, fMLF induces a moderate increase in NO and intracellular cGMP concentration as compared with the increases invoked by most NO donors (48), most likely because of the low NOS expression level in the terminally differentiated granulocytes (63,64). The small increase in intracellular cGMP is associated with enhanced neutrophil functions such as degranulation and chemotaxis (48).…”
Section: Discussionmentioning
confidence: 56%
“…Moreover, addition of hydrogen peroxide to Nv-hydroxy-L-arginine in a cell free system also resulted in nitrite release. Finally, recent data demonstrated that denitrification Nv-hydroxy-L-arginine by human neutrophils does not release NO but directly leads to nitrite/nitrate formation instead [17]. Interestingly, NAGASE et al [18] showed that hydrogen peroxide also releases NO from L-arginine, as confirmed by chemiluminescence.…”
Section: Discussionmentioning
confidence: 95%